Effects of total saponins from Rhizoma Dioscoreae Nipponicae on expression of vascular endothelial growth factor and angiopoietin‐2 and Tie‐2 receptors in the synovium of rats with rheumatoid arthritis. Issue 5 (May 2016) - Guo, Yachun; Xing, Enhong; Liang, Xiujun; Song, Hongru; Dong, Wenjuan
Abstract : Background : This study aimed to determine the effects of total saponins from Rhizoma Dioscoreae Nipponicae (TS‐RDN) on the expression of vascular endothelial growth factor (VEGF) and angiopoietin (Ang)‐2 and Tie‐2 (endothelial tyrosine kinase receptor) receptors in the synovium of rats with rheumatoid arthritis (RA) (collagen‐induced arthritis; CIA), and to examine the mechanisms of TS‐RDN in alleviating RA. Methods : The CIA rat model was established and the animals were randomly divided into control, CIA model, TS‐RDN, diosgenin, and tripterygium groups. Fluorescent polymerase chain reaction was performed to detect VEGF expression in the rat knee joint synovium. Additionally, immunohistochemical assay was used to detect protein expression of Ang‐2 and Tie‐2 in the rat knee joint synovium. Results : Expression of VEGF, Ang‐2, and Tie‐2 in the model group was significantly higher than in the control group ( p < 0.01). After TS‐RDN, tripterygium and diosgenin treatment, VEGF and Ang‐2 expression was lower than in the model group ( p < 0.01). However, Tie‐2 expression showed no significant difference. The effects of TS‐RDN on VEGF expression were more marked than those of tripterygium and diosgenin ( p < 0.01). Conclusion : TS‐RDN might reduce the expression of VEGF, Ang‐2, and Tie‐2 in the synovium, thus inhibiting synovial angiogenesis and playing a therapeutic role in RA.